PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI MENGGUNAKAN MODEL DISCOVERY LEARNING DI KELAS V SDN 08 MARUNGGI KOTA PARIAMAN - Rima Lailatul Hasanah; Elfia Sukma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the students' ability to write descriptive text which was still relatively low. This is because teachers are not yet optimal in utilizing appropriate learning models in the learning process. This research aims to describe the improvement of descriptive text writing skills using the Discovery Learning model in class V of SDN 08 Marunggi Kota Pariaman. This type of research is Classroom Action Research using qualitative and quantitative approaches. This research was carried out in two cycles, each cycle consisting of planning, implementation, observation and reflection stages. This research data is in the form of qualitative and quantitative data. The research data sources were obtained from the learning process (teacher and student activities) and assessment of attitudes, knowledge and skills. The subjects in this research were 28 class V teachers and students at SDN 08 Marunggi, Pariaman City. The results obtained in this research show that: a) the teaching module has increased from cycle I which had an average percentage of 87.49% with good qualifications (B) to 95.83% with very good qualifications (A) in cycle II, b ) the implementation of teacher and student aspects showed an average in cycle I of 84.37% with good qualifications (B) increasing to 93.75% with very good qualifications (A) in cycle II, c) assessment of descriptive text writing skills Students in cycle I obtained an average of 72.11% with sufficient qualifications (C) increasing to 84.72% with good qualifications (B) in cycle II. It can be concluded that the Discovery Learning model can improve the descriptive text writing skills of students in class V of SDN 08 Marunggi Kota Pariaman.